Mastering Concurrency Programming with Java 9 - Second Edition - Gonzalez, Javier Fernandez (Packt Publishing Limited, 2017)
bMaster the principles to make applications robust, scalable and responsive/bh2About This Book/h2ulliImplement concurrent applications using the Java 9 Concurrency API and its new components/liliImprove the performance of your applications and process more data at the same time, taking advantage of all of your resources/liliConstruct real-world examples related to machine learning, data mining, natural language processing, and more/li/ulh2Who This Book Is For/h2This book is for competent Java developers who have basic understanding of concurrency,
Keywords: COMPUTERS / Programming / Parallel; COMPUTERS / Programming Languages / General